FAKTOR-FAKTOR YANG MEMENGARUHI KEPUTUSAN NASABAH DALAM MEMILIH PEGADAIAN SYARIAH KABUPATEN GROBOGAN (Equilibrium: Jurnal Ekonomi Syariah, 2016)
This study used field research approach by questionnaire distributed to Grobogan Sharia pawnshop costumers, 113 respondents. Data were analyzed using multiple regression analysis. The findings of this study were: 1) Cultural factors have influence on the service usage decision of Grobogan Islamic pawnshop with tcount 7.051> ttable 1.967 and significance level below 5 %; 2) Social factors have influence on the service usage decision of Grobogan Islamic pawnshop with tcount 2.487> ttable 1.967 and significance level below 5%; 3) personality factors have influence on the service usage decision of Grobogan Islamic pawnshop with tcount 7.497> ttable 1.967 and significance level below 5%.